Aproximación a la vitalidad de la lengua nasa yuwe en dos comunidades de habla nasa: contraste sociolingüístico (2020)
In recent decades, the loss of minority languages around the world has received special attention among scholars and activists. The identification of the ethnolinguistic vitality of minority languages is crucial to create strategies for their maintenance. This thesis aims to identify and compare the ethnolinguistic vitality in two settlements of the Nasa people: Path Yu’ and Huila. The former locates migrants from different settlements of the Nasa people in the municipality of Páez (Department of Cauca, Colombia), which are survivals of an earthquake in 1994. The latter is made up of Nasa people who remained in their ancestral territories despite the circumstances caused by the earthquake (Olson & Sarmiento, 1995). This research used a mixed methodological approach with a dominant qualitative component. It integrated ethnographical tools, such as participant observation, interviews, focus groups, and life stories. Additionally, it included a quantitative sociolinguistic test. The sample was of the 2.5% and 10% of the population of Huila and Path Yu’. The sociolinguistic test showed that, in Huila, the Nasa Yuwe language is in a high state of maintenance. The 93% of the sample is bilingual in Nasa Yuwe and Spanish. The qualitative tools support this result; the community members always communicate in Nasa Yuwe with their interlocutors. According to the scale of vitality of the Endangered Languages Catalogue (ELCat), the Nasa Yuwe in this shelter is "vulnerable". The results also indicate a strong intergenerational transmission of the Nasa Yuwe, since the child population is monolingual in Nasa Yuwe until 7 years old. In most cases, the Nasa Yuwe is the first language that children learn in Huila. In contrast, the results of the sociolinguistic test in Path Yu’ show that the Nasa Yuwe language in this shelter is in a state of increasing loss. The 60% of the sample is bilingual in Nasa Yuwe and Spanish, with a higher domain on Spanish. The people in Path Yu’ only communicate in Nasa Yuwe on limited occasions, depending on the interlocutor. Elders communicate among them in this language; but older adults and young people communicate in Spanish. Following the scale of vitality of the ELCat, the Nasa Yuwe is "severely endangered" in Path Yu’. There is a weak intergenerational transmission of Nasa Yuwe and children are mainly monolingual in Spanish, although there are exceptional cases in which they are bilingual. This research contributes to the understanding of the sociolinguistic situation in both Huila and Path Yu’ settlements. The comparison of both contexts gives lights on the motivations and causes behind the language maintenance and loss among the Nasa Yuwe speakers in the region. This research will thus afford the basis of future strategies for the maintenance and revitalization of Nasa Yuwe.